(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article identifies the key elements of the effective didactic use of video in the educational process and the attempts to answer the following questions are made: what kind of video can achieve the greatest didactic effect? What should be changed today in didactic approaches and methods? What are the positive aspects and disadvantages of using video in the educational process? To understand how to implement video in the learning process competently from a didactic point of view, it is necessary to study the types of educational videos, the concept of their use and the criteria for effective teaching videos. The author of this article being a member of the PRINTeL project took a ToT course on “Video as a Learning Tool for Teachers and Students//Video Lecturing and Promoting Interaction in the Classroom” at the University of Porto (Portugal) in November 2018. The methodological basis of this study were the works of Z. Woolfitt, A.W. Bates, J. Day, C. Clark & R. Mayer, A. Deal, L. Germany, P. Gorissen, J. Koumi. The purpose of the research carried out within the framework of this article is to analyze the existing types of educational videos, the concepts of their use and the criteria for effective teaching videos. The use of new tools or approaches to learning should be based on a holistic view of the needs of all students, the subject area and learning objectives, and not on the false idea of what this modern generation of students’ demands from us. If we want to use all the advantages of video lectures and introduce this technology into our educational process effectively, then teachers need appropriate and adequate support for this in the form of staff advanced training.